(untitled) (CIPEEX, 2025)
Due process of law, based on the guarantee of a fair and equitable process for all parties involved, is an essential pillar of the legal system, as advocated by Beccaria. In the specific context of wage garnishment, the Brazilian Civil Code is present, ensuring that due process is observed, preserving the fundamental rights of both the parties involved and the creditor and debtor. Despite being a fundamental value in Brazilian law, the principle of due process faces significant challenges, such as procedural slowness and the lack of universal access to justice. Given this, the following question arises: how can we guarantee the effectiveness of due process in the enforcement of wage garnishment? The general objective of this project is to analyze the effectiveness of due process in the execution of wage garnishment. The following specific objectives were formulated: i) to discuss the doctrinal concept of due process of law; ii) to address the legal provision for due process of law in the Brazilian legal system; iii) to analyze the (in)effectiveness of due process of law in the execution and garnishment of wages. In order to achieve the proposed objectives, bibliographical reviews will be carried out using works by renowned authors, such as Beccaria, and consulting the Code of Civil Procedure (CPC) and the Federal Constitution (CF). In addition, information available on specialized websites and case law related to the topic will be analyzed. This article aims to highlight the importance of due process for society, science and the judiciary, highlighting its relevance in promoting justice, social stability, the validity of academic research and the impartiality of judgments. In addition, it seeks to identify challenges and possible improvements in the effectiveness of this principle in the execution of wage garnishment. It can be seen that the Code of Civil Procedure establishes garnishment as a measure to protect the debtor against excessive rights in the relationship of obligation. However, in forensic practice, situations arise in which the creditor can be harmed due to insoluble debts and debtors, highlighting the complexity and challenges of the effective application of due process of law in the execution of wage garnishment.